Historical Juridical Study on the Amendment of Law Number 32 of 2004 Juncto Law Number 23 of 2014 concerning Regional Government - Ahmad Fanani (Rechtenstudent, 2023)
In Each region there is a regional government that has been regulated in the applicable laws and must be obeyed, but in this case the regional government laws and regulations are dynamic. So that the statutory regulations undergo a change from time to time according to developments in their time. The focus of this research is 1) How is the organizational structure and authority of the Change of Law Number 32 of 2004 to Law Number 23 of 2014. 2) How is the political dynamics that occur as a result of the Transition of Law Number 32 of 2004 to Law Number 23 of 2014. 3) What are the positive and negative impacts of changing the law. This research is about regional government, according to article 18 paragraph (1) that Indonesia is a unitary state. Therefore, in each region there is a government that regulates each region. There are provincial and district/city governments. So Law Number 32 of 2004 was formed which regulates regional government. Although in the end it changed to Law Number 23 of 2014 concerning Regional Government. In this case the changes are related to changes in the organizational structure and authority of the local government. Because local government laws are dynamic, the laws and regulations that underlie the procedures for administering regional government also need to be updated and improved. But these changes did not occur significant changes.